Water, sanitation and hygiene (WaSH) facilities and its link to diarrhea at the eco-zones of Abra de Ilog, Occidental Mindoro, Philippines - Paro, Fevi Rose Cortezano (College of Public Health,University of the Philippines Manila, 2018)
Eco-zones, which differ in socio-environmental characteristics, have varying accessibility to resources like water. Variability in water sources influence hygiene practices, and sanitation facilities as well as WaSH-related impacts like diarrheal diseases. This ecologic study aimed to determine the link between water, sanitation and hygiene (WaSH) facilities and diarrhea at the different eco-zones: upland, lowland, coastal areas in the municipality of Abra de Ilog Occidental Mindoro. A total of 418 families served as respondents with 162 households from the coastal eco-zone, 142 and 114 from the lowland and upland eco-zones, respectively. Mixed participatory methods, collecting both quantitative and qualitative data were used in the study. Descriptive statistics and WaSH transect mapping were used for the data analysis. Results showed thatm upland eco-zone had the least proportion of households with: (1) improved drinking water facility, (2) sanitary toilets and (3) fair hygiene practices. The upland eco-zone also had the highest proportion of households with diarrhea (64.04%) regardless of whether they have complete, incomplete or no WaSH facility at all, followed by the coastal (34.57%) and lowland (16.20%) eco-zones. Further, more than 60% of households having incomplete facilities ? drinking water and handwashing facilities only ? had experienced diarrhea. Hence, in this case, the absence of toilet facilities, increases the occurrence of diarrheal diseases,. In conclusion, having incomplete WaSH facilities will more likely lead to the occurrence of diarrhea irrespective of eco-zone. Nonetheless, having incomplete facilities is relatively better than not having any facility at all. This means that the presence of a WaSH facility, even ifit is incomplete, is a useful factor against diarrhea occurrence and these trends apply to all cases in the upland, lowland and coastal communities.